Building Attitudes in Financial Management Behavior of Garut University Students through Financial Management-Based Training - Hadita, Akmala; Wufron, Wufron (Universitas Negeri Semarang, 2022)
The results of a pre-research survey on the behavior of financial management of Garut University students proved to be not good because they did not understand the importance of saving and using money. This study aims to determine the influence of financial attitudes on the behavior of financial management of university students in garut training based on financial management. The research method used in this study is a mix of qualitative and quantitative methods. The data analysis method used is regression analysis with moderation variables. The data were obtained by distributing a research questionnaire to 100 students from the sampling results. The results showed a positive and significant effect on the behavior of financial management of garut university students. Financial management training can moderate the influence of financial attitudes on the financial management behavior of garut university students. Financial management training can strengthen the influence of attitudes towards student financial management behavior. The findings in this study are that financial management training as a supplement and complement to the curriculum that already exists at Garut university needs to be carried out consistently because it is proven to strengthen the influence of attitudes on student financial management behavior. This research is important to carry out to increase knowledge, values, attitudes and competencies in financial management for students in determining financial management decisions.